Impacts of bovine traceability implantation in computerized rural companies: case studies (Journal of Information Systems and Technology Management, 2007)
This study looked into evaluating the impacts that the adhesion to the bovine traceability caused in four agricultural companies that adopted or used ITs for tracked herd management. After comparing the case studies it was concluded that the adhesion to traceability caused the adoption of ITs, mainly of the management and traceability system for beef cattle and the electronic scale; the zoo technical changes that happened were, the individual identification of the animals, the control of animal stock and the possibility to determine performance and reproductive indexes; the management changes that happened were the development of new controls by filing the animal identification document (DIA), the documentation of the purchase, use and exit of inputs (nutritional and sanitarian), and the documentation of animal movements. It was not verified the return of managerial or zoo technical information by SISBOV that aided the companies in their decision-taking process.